The fully integrated engineer : combining technical ability and leadership prowess - Cerri, Steven T. (IEEE PCS professional engineering communication series., 2016)
College teaches you to be a good engineer. But it's likely that your college engineering courses didn't have time to teach you how to effectively contribute your ideas or how to transition to management or leadership. This book provides you with those missing tools. *Identify patterns of behavior that don't serve you (or your organization) well and change them *Create a plan of action that will allow for personal change that will impact your professional work *Hone the ways that your technical work can be seen positively inside your organization *Promote the talents and skills of the team players around you *Become a flexible, supportive, and positive asset.